2022
DOI: 10.3390/jcm11030519
|View full text |Cite
|
Sign up to set email alerts
|

Metal Allergy Mediates the Development of Oral Lichen Planus via TSLP-TSLPR Signaling

Abstract: Metal allergy is a T-cell-mediated delayed type of hypersensitive reaction. The pathogenetic mechanisms underlying the allergy are unclear, although the condition has been reported to be related to oral lichen planus (OLP), despite an absence of immunological studies to support this relationship. In this study, histopathological samples of OLP patients were examined to compare the metal allergy-positive and -negative groups, with a focus on the network of epidermal keratinocytes and T cells induced by thymic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In general, past studies have focused on dental metals and some smaller series have reported associations with fragrance, avoring, and preservative allergens. 10,11,13,[30][31][32] While metals and dental lling products can often be traced to a de ned source, the high burden of allergy to fragrance, avorings, and preservatives seen in our cohort is important and highlights the clinical di culty contact allergy may present in OLP since these allergens are often less apparent, more di cult to trace, and harder to avoid. The connection between these allergy ndings and clinical OLP phenotype or progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, past studies have focused on dental metals and some smaller series have reported associations with fragrance, avoring, and preservative allergens. 10,11,13,[30][31][32] While metals and dental lling products can often be traced to a de ned source, the high burden of allergy to fragrance, avorings, and preservatives seen in our cohort is important and highlights the clinical di culty contact allergy may present in OLP since these allergens are often less apparent, more di cult to trace, and harder to avoid. The connection between these allergy ndings and clinical OLP phenotype or progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[6][7][8] Multiple case-series have emerged documenting cutaneous allergy in OLP. [9][10][11][12][13][14][15] One study has proposed that contact allergy, at least to metal, could initiate pathogenesis. 11 However, it is not generally known to what extent contact allergy drives pathogenesis or if avoidance improves disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expansion of T cells at the lesion site collaborated with the formation of the oral lichen planus (OLP). T cells infiltration via TSLP-TSLP-receptor (TSLPR) signaling, and TNF-α production was higher in OLPs in metal-allergy patients compared to healthy controls [ 77 ].…”
Section: Mechanisms and Biomarkersmentioning
confidence: 99%